Is PTSD overdiagnosed?. (5th May 2021) - Tully, John; Bhugra, Dinesh; Lewis, Stephanie J; Drennan, Gerard; Markham, Sarah
Abstract : Some of the burgeoning rates of PTSD diagnosis are attributable to broadened disease definitions, say John Tully and Dinesh Bhugra . But Stephanie J Lewis, Gerard Drennan, and Sarah Markham argue that underdiagnosis, not overdiagnosis, may be the greater problem